Identifikasi Kesulitan Belajar Metodologi Penelitian Mahasiswa Pendidikan Guru Sekolah Dasar - Raissa Rahmah; Rani Amelia; Jesi Alim; Mitha Anggriani (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2025)
This study identification the learning difficulties faced by Primary School Teacher Education (PGSD) students in the Research Methodology course. The course is crucial as it provides the foundation for academic writing and thesis completion, yet many students encounter obstacles in mastering the concepts. This research employed a quantitative descriptive survey design. Data were collected from 37 randomly selected students of the 2023 cohort through a Likert-scale questionnaire covering five indicators: attention, material comprehension, memory, learning interest, and motivation. The findings revealed that students’ learning difficulties ranged from moderate to high, with material comprehension being the most dominant challenge (65.94%, high category). Other aspects such as attention, memory, interest, and motivation were categorized as moderate. These results indicate that the complexity of methodological concepts, low retention, and lack of interest and motivation hinder students’ academic progress. Therefore, more interactive, applicative, and varied teaching strategies, alongside efforts to strengthen motivation and reading persistence, are essential to support students’ academic readiness. The implications of this study emphasize the need for innovative learning strategies to improve methodological understanding and prepare PGSD students as competent future teachers.